Decriminalization of drug use. Issue 4 (July 2018) - Vicknasingam, Balasingam; Narayanan, Suresh; Singh, Darshan; Chawarski, Marek
Abstract : Purpose of review: To review the literature on decriminalization of drug use from 2016 to 2017 and suggest the way forward. Recent findings: The systematic review of the literature on decriminalization resulted in seven articles that discuss decriminalization as compared with 57 published articles on legalization. Decriminalization of drug use did not have an effect on the age of onset of drug use and the prices of drugs did not decrease after the implementation of drug decriminalization. Policy-based studies on decriminalization suggest shifting from criminal sanctions to a public health approach, which was endorsed by the United Nations (UN) that viewed drug addiction as a preventable and treatable health disorder. One study preferred decriminalization only for cannabis and cautioned against regulating cannabis like alcohol. Another study indicated that general medical practitioners in Ireland did not favour the decriminalization of cannabis. Summary: Scientific evidence supporting drug addiction as a health disorder and the endorsement by the UN strengthen the case for decriminalization. However, studies reporting on the positive outcomes of decriminalization remain scarce. The evidence needs to be more widespread in order to support the case for decriminalization. Furthermore, the endorsement by the UN needs to be acted upon by individual member states.